Non-Prescription Use of Proton-Pump Inhibitors for Self - Treating Frequent Heartburn (Medical Forum Monthly, 2022)
Objective: Determine the Prescription Patterns of Proton Pump Inhibitors (PPI) at the outpatient department (OPD) of a tertiary care hospital of Sindh.Study Design: Retrospective studyPlace and Duration of Study: This study was conducted at the Department of Pharmacologhy and Medicine, Peoples University of Medical and Health Sciences for Women from February 2019 to August 2020.Materials and Methods: Previous records of 300 outpatient department (OPD) subjects were checked during the study period. OPD sample was selected by probability non – purposive convenient sampling. Age, gender and GI symptoms PPI used for were entered in proforma. PPI class, duration of use, frequency of use, and prescription or non-prescription patterns were noted. Data variables were saved in a pre – structured proforma. Data was analyzed on SPSS (version 21.0) and Microsoft Excel sheet. Data was presented as tables showing frequency and % of variable.Results: Omeprazole was used by 31% followed by dexlansoprazole 29%, esomeprazole 21%, pantoprazole 7.3%, lansoprazole 7.6% and rabeprazole by 4% of subject’s respectively (table - 2). PPI were being used as long durations as >5 years noted in 18.6% on irregular basis (35.6%) and without prescription (63.0%).Conclusion: We found injudicious use of proton pump inhibitors on irregular basis without prescription that needs to be controlled by the health authorities.